Case report: Aggressive natural killer cell leukemia and refractory hemophagocytic lymphohistiocytosis in an adolescent - Spaner, Caroline; Durkee-Shock, Jessica; Weng, Andrew; Stubbins, Ryan; Gerrie, Alina S.; Pittaluga, Stefania; Cohen, Jeffrey I.; Chen, Luke Y. C. (Frontiers in Hematology, 2024)
Aggressive natural killer cell leukemia (ANKL) is a rare, aggressive hematologic malignancy which often presents as fulminant Epstein-Barr virus (EBV)- driven hemophagocytic lymphohistiocytosis (HLH). ANKL lacks a distinct immunologic and morphologic signature, making early diagnosis particularly challenging. Here we present a case of ANKL in a patient presenting with EBV-HLH. After poor treatment response to the HLH-2004 protocol (etoposide and dexamethasone), bone marrow biopsy demonstrated an atypical CD3-/CD56+ natural killer (NK) cell population with diminished CD7 expression consistent with EBV+ ANKL. Asparaginase-based chemotherapy was initiated but his disease progressed and he died from multiorgan failure. This case highlights the diagnostic challenges of ANKL given the lack of standardized diagnostic criteria, the importance of considering T/NK cell malignancies in the differential diagnosis of EBV-HLH, and adds to the literature on this rare disease.